CysQ of , a Protozoa, May Have Been Acquired from Bacteria by Horizontal Gene Transfer - Ji Young Lee; Sangsoo Kim (Genomics & Informatics)
Horizontal gene transfer (HGT) is the movement of genetic material between kingdoms and is considered to play a positive role in adaptation. Cryptosporidium parvum is a parasitic protozoan that causes an infectious disease. Its genome sequencing reported 14 bacteria-like proteins in the nuclear genome. Among them, cgd2_1810, which has been annotated as CysQ, a sulfite synthesis pathway protein, is listed as one of the candidates of genes horizontally transferred from bacterial origin. In this report, we examined this issue using phylogenetic analysis. Our BLAST search showed that C. parvum CysQ protein had the highest similarity with that of proteobacteria. Analysis with NCBI's Conserved Domain Tree showed phylogenetic incongruence, in that C. parvum CysQ protein was located within a branch of proteobacteria in the cd01638 domain, a bacterial member of the inositol monophosphatase family. According to Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, the sulfate assimilation pathway, where CysQ plays an important role, is well conserved in most eukaryotes as well as prokaryotes. However, the Apicomplexa, including C. parvum, largely lack orthologous genes of the pathway, suggesting its loss in those protozoan lineages. Therefore, we conclude that C. parvum regained cysQ from proteobacteria by HGT, although its functional role is elusive.